2013
DOI: 10.1103/physrevb.87.195435
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and spin magnetic moments of transforming one-dimensional iron inside metallic and semiconducting carbon nanotubes

Abstract: The orbital and spin magnetic properties of iron inside metallic and semiconducting carbon nanotubes are studied by means of local x-ray magnetic circular dichroism (XMCD) and bulk superconducting quantum interference device (SQUID). The iron-nanotube hybrids are initially ferrocene filled single-walled carbon nanotubes (SWCNT) of different metallicities. We show that the ferrocene's molecular orbitals interact differently with the SWCNT of different metallicities with no significant XMCD response. At elevated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…In this contribution we report a neat method for magnetic nanostructuring within a single-wall carbon nanotube (SWCNT) 12 13 14 15 16 17 18 , that is an advanced conductor with tunable metallicity 19 20 . Ensembles of fcc nickel nano clusters have been produced in designer mean dimensions inside SWCNT bundles.…”
mentioning
confidence: 99%
“…In this contribution we report a neat method for magnetic nanostructuring within a single-wall carbon nanotube (SWCNT) 12 13 14 15 16 17 18 , that is an advanced conductor with tunable metallicity 19 20 . Ensembles of fcc nickel nano clusters have been produced in designer mean dimensions inside SWCNT bundles.…”
mentioning
confidence: 99%
“…At the same time, the experimental studies of encapsulation inside single-walled nanotubes are rather scarce. 11,12 The situation is opposite for theoretical studies. Most ab initio calculations of electronic and magnetic properties were conducted for singlewalled carbon NT filled with transition metal nanowires.…”
Section: Nanostructures At Low Temperaturesmentioning
confidence: 86%
“…[13][14][15][16][17][18][19][20][21] Using NTþTM as memory elements for magnetic recording implies sufficient internal anisotropy. However, several experimental magnetization studies 6,12 have shown that NTþTM exhibit superparamagnetic behavior, which is unsuitable for memory elements. One of the reasons for this behavior is that the existing technologies for filling NT with metal result in the formation of metal clusters within the nanotube, which consist of several tens of atoms and are separated from each other.…”
Section: Nanostructures At Low Temperaturesmentioning
confidence: 98%
“…The magnetisation per nickel atom has been evaluated by taking the nickel atomic concentration derived from the XPS data into account (see ESI, section 4 †). 27 The magnetisation curves are linear at magnetic fields up to ±0.7 T for 3D-Ni(acac) 2 , ±0.8 T for 1D-Ni (acac) 2 @NT2.1 and ±0.9 T for 1D-Ni(acac) 2 @NT1.3 so that according to the Curie law we can calculate the effective…”
mentioning
confidence: 95%